Legal Protection of The Right to Education of Street Children Working in Sidoarjo District - Elisabeth Melanie Saraswati; Eny Sulistyowati; Iqian Amienudin Lanov (Universitas Negeri Surabaya, 2024)
The phenomenon of street children who work is one of the issues in Indonesia which until now the problem is still experienced in many areas. Children are one of the protected groups or groups of society so that the phenomenon of street children is a serious issue because it relates to the fulfillment of children's rights. Education, as one of the most important rights that a child is entitled to, certainly needs attention, especially among street children. Legal protection of the educational rights of street children working in Sidoarjo Regency includes the implementation of Article 8 paragraph 1 of East Java Governor Regulation Number 33 of 2018 through coaching. The coaching is carried out by the Sidoarjo Regency Social Service with the cooperation of the East Java Provincial Social Service through the Youth Development Social Service (UPT PSBR) as the government agency responsible for fulfilling it. This writing is included in empirical legal writing, namely the approach method used is qualitative, producing descriptive data poured through oral or written from phenomena on certain behaviors, so that more emphasis is placed on data quality. The research location is in Sidoarjo Regency, precisely in the Square. The results of this study indicate that there are still street children in Sidoarjo Regency who have difficulty carrying out their education and there are internal and external constraints from the relevant government parties so that there are limitations in fulfilling the right to education for street children.